Advances in the role of the GADD45 family in neurodevelopmental, neurodegenerative, and neuropsychiatric disorders - Huang, Mengbing; Wang, Ji; Liu, Wei; Zhou, Hongyan (Frontiers in Neuroscience, 2024)
The growth arrest and DNA damage inducible protein 45 (GADD45) family comprises stress-induced nuclear proteins that interact with DNA demethylases to facilitate DNA demethylation, thereby regulating diverse cellular processes including oxidative stress, DNA damage repair, apoptosis, proliferation, differentiation, inflammation, and neuroplasticity by modulating the expression patterns of specific genes. Widely expressed in the central nervous system, the GADD45 family plays a pivotal role in various neurological disorders, rendering it a potential therapeutic target for central nervous system diseases. This review presented a comprehensive overview of the expression patterns and potential mechanisms of action associated with each member of GADD45 family (GADD45α, GADD45β, and GADD45γ) in neurodevelopmental, neurodegenerative, and neuropsychiatric disorders, while also explored strategies to harness these mechanisms for intervention and treatment. Future research should prioritize the development of effective modulators targeting the GADD45 family for clinical trials aimed at treating central nervous system diseases.